Efeito das células mononucleares no tratamento da estenose vascular em camundongos hipercolesterolêmicos - Lima, Leandro Ceotto Freitas (2012)
Vascular remodeling with neointimal formation is an adaptive process that occurs in response to chronic changes in hemodynamic conditions such as atherosclerosis. Spleen derived mononuclear cells (MNC) have been implicated in neovascularization. Therefore, the aim of this study was to evaluate in situ MNC treatment after carotid artery stenosis in ApoE-/- mice. Experiments were performed in 5-month-old female ApoE-/- mice. Animals were splenectomized and underwent left common carotid artery stenosis by placing a cuff around it. Ten days later the cuff was removed and animals received an in situ application of 20 µl saline (Saline; n = 8) or 106 splenic MNC (MNC; n = 6), isolated from GFP mice. A third group (CT; n = 5), received no treatment, it was being used as a vascular remodeling parameter. After 7 days, animals were euthanized, perfusion-fixed and the whole left common carotid artery was excised for histomorphological analysis and the plasma for biochemical analysis. Tissue sections (10 µm) were stained with Oil-Red-O and hematoxilin-eosin for plaque and morphological analysis. To localize the MNC, we used GFP fluorescence and CD90-PE/CD117-FITC to localize EPC. To apoptosis and reactive oxygen species detections was used TUNEL and DHE respectively. Mean±SEM, 1 way ANOVA followed by Tukey post hoc and Student t test. *p<0.05. The GFP expressing cells revealed that MNC was presenting at endothelial layer in the treated group and the EPC was confirmed at CD-90/CD117 positive. This treatment decreased the thickening of carotid intima layer (MNC: 29.5±11.2** vs. Saline: 104±15.9 vs. CT: 27.4±7.1 103 µm2 ) and, consequently, augmented vessel lumen (MNC: 72.5±8.6** vs. Saline: 7.8±4.6 vs. CT 52.6±2.7 103 µm2 ). In addition, there was no difference in vessel external area between the groups (Saline: 115±18.4 vs. MNC: 113.9±10.2 vs. CT: 89.7±5.8 103 µm2 ) suggesting no positve vascular remodeling, evidenced by wall/lumen (Saline: 2.94±0.47 vs. MNC: 0.6±0.08** vs. Control: 0.7±0.07) and remodeling ratio (Saline: 0.92±0.37 vs. MNC: 0.92±0.21). Furthermore, the treatment was be able to reduce reactive oxygen species and consequently apoptosis. Our data suggest that MNC therapy augments common carotid artery luminal area without evidence of vascular remodeling, probably due to the paracrine action of MNC, which could promote endothelial cells repairment on the injured vascular wall